2011
DOI: 10.1177/0022219411422260
|View full text |Cite|
|
Sign up to set email alerts
|

Internalizing Problems of Adults With Learning Disabilities

Abstract: In this article the authors report a meta-analysis that examines the association between internalizing problems (anxiety and depressive symptoms) and learning disabilities (LD) in adults. Two hypotheses about the relationship between internalizing problems and LD in adults are posited and tested: the abeyance hypothesis (internalizing problems decline in adulthood) and the continuance hypothesis (internalizing problems continue in adulthood). From an initial pool of 171 relevant studies, 15 studies met the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 40 publications
5
56
0
2
Order By: Relevance
“…For instance, the study [11] shows that 14.2%, both children and adolescents, experienced severe depression and 23.8% of them showed severe anxiety problems. The results of a current meta-analysis [12] with young adults support the continuity of internalizing disorders, as adults with reading disabilities continue to present such disorders in a similar way to that of children and adolescents. However, other studies indicate that difficulties decrease in students with learning disabilities as age increases.…”
Section: Emotional and Motivational Problems In Spanish-speaking Adolsupporting
confidence: 52%
“…For instance, the study [11] shows that 14.2%, both children and adolescents, experienced severe depression and 23.8% of them showed severe anxiety problems. The results of a current meta-analysis [12] with young adults support the continuity of internalizing disorders, as adults with reading disabilities continue to present such disorders in a similar way to that of children and adolescents. However, other studies indicate that difficulties decrease in students with learning disabilities as age increases.…”
Section: Emotional and Motivational Problems In Spanish-speaking Adolsupporting
confidence: 52%
“…These different reading disorders have different causes and require different interventions, and the authors highlight that neither disorders lend themselves to categorical diagnosis. Irrespective of what form of disorder a student experience, they involve literacy problems which may cause difficulties for education, employment, and well-being (Goldstein, Naglieri, & DeVries, 2011;Klassen, Tze, & Hannok, 2013;Reiff, Hatzes, Bramel, & Gibbon, 2001). …”
Section: An Important Factor Impeding a Self-autonomous Learning Procmentioning
confidence: 99%
“…The presence of literacy problems and weak GPA may have several unfortunate consequences, such as depression, anxiety, loneliness and poorer quality of life (Ginieri-Coccossis et al, 2013;Klassen et al, 2013), more frequent risk behaviour, substance use, aggressive and delinquent acts (McNamara & Willoughby, 2010), as well as drop-out from school (Goldstein et al, 2011). Yet, more adolescents with literacy problems attend higher education than before.…”
Section: Cognitive/school-related Factorsmentioning
confidence: 99%
“…Similarly, most adults in Ingesson's (2007) study acknowledged that having dyslexia influenced their school achievement and those still in school were less optimistic about their future than adults who had left school, including the unemployed (Ingesson, 2007). Klassen et al (2013) found that adult students with LD did not differ on levels of internalizing disorders compared to adults with LD in the general population. Given conflicting findings in previous research, it is not clear to what extent challenges associated with LD, including RD, are limited to the school context.…”
Section: Discussionmentioning
confidence: 93%